2011
DOI: 10.1007/s00170-011-3593-y
|View full text |Cite
|
Sign up to set email alerts
|

Storage location assignment and order picking optimization in the automotive industry

Abstract: The objective of this study is to design storage assignment and order picking system using a developed mathematical model and stochastic evolutionary optimization approach in the automotive industry. It is performed in two stages. At the first stage, storage location assignment problem is solved with a class-based storage policy with the aim of minimizing warehouse transmissions by using integer programming. At the second stage, batching and routing problems are considered together to minimize travel cost in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 15 publications
0
34
0
1
Order By: Relevance
“…Thus, storage policies, which assign SKUs to storage locations, generally fall into three broad categories, presented by Hausman et al, in 1976, which are class-based storage, randomized storage, and dedicated storage [21]. Class-based storage policy distributes products into classes and for each class it reserves a region within the storage area in which the products are located in any way [12,20,[22][23][24]. A dedicated storage policy reserves each storage location for a specific product and no other products can be stored in that location [6,13,25].…”
Section: Storage Location Assignment Problem (Slap)mentioning
confidence: 99%
“…Thus, storage policies, which assign SKUs to storage locations, generally fall into three broad categories, presented by Hausman et al, in 1976, which are class-based storage, randomized storage, and dedicated storage [21]. Class-based storage policy distributes products into classes and for each class it reserves a region within the storage area in which the products are located in any way [12,20,[22][23][24]. A dedicated storage policy reserves each storage location for a specific product and no other products can be stored in that location [6,13,25].…”
Section: Storage Location Assignment Problem (Slap)mentioning
confidence: 99%
“…Verschure (2014) valuated the order pick process in a warehouse and compared the effectiveness of picking process with respect to the information availability and batch size. Ene and Öztürk (2012) revealed the key factors, including time interval and storage location proximity, impacting the order picking operations in the warehouse. The study indicated that over half of the warehouse operating costs were incurred in order picking process.…”
Section: Warehouse Operations and Technologymentioning
confidence: 99%
“…Although there are many research results of store-space assignment in the traditional person to goods picking pattern [2][3][4][5][6] , but the essential difference between the person to goods picking pattern and goods to person picking pattern, the research results of person to goods picking pattern cannot be directly applied to the store-space assignment of goods to person picking pattern. In the present literature, there are few studies on the related issues based on goods to person picking patterns.…”
Section: Introductionmentioning
confidence: 99%